Balanced-integration: A dimension of supervision to support students navigating parenthood in pursuit of a PhD: - Nkoala, S. (South African Journal of Higher Education, 2024)
This article explores the experiences of doctoral students juggling parental and professional roles. It proposes a balanced-integration approach in the reflective supervisor framework to tailor support. The research focuses on identifying challenges and evaluating the approach’s effectiveness, suggesting supervisors should serve as advocates for well-being and motivation. With the South African government’s National Development Plan aiming for a higher education sector that can produce more than 100 doctoral graduates per one million of the population by 2030, it is imperative to understand PhD student’s simultaneous identities as parents and professionals who must balance the demands of their studies, families and careers. The study advances a balanced-integration approach for supervising this demographic, with supervisors serving as advocates for the holistic well-being of these students, architects of personalised academic pathways, and catalysts for motivation inspired by family commitments. This approach adds a fifth dimension to Pearson and Kayrooz’s four factors of facilitative supervisory practice. The methodology is a descriptive quantitative study research design and a cross-sectional approach based on online surveys completed by 47 respondents from 13 South African higher education institutions and eight from abroad (n = 55).